Alumina ceramic doped magnesium carbon refractory brick and preparation method thereof
Patent Information
- Application Number
- CN202610621264.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-08
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-05-08
AI Technical Summary
[0003]针对现有传统镁碳耐火砖存在的抗氧化性不足、低碳化与性能失衡、高温结构稳定性差、抗渣侵蚀弱等问题
[0021]I. This invention addresses the problems of insufficient oxidation resistance, performance imbalance after low-carbonization, poor high-temperature structural stability, and weak slag erosion resistance in traditional magnesia-carbon refractory bricks through the synergistic design of core-shell modified fused magnesia aggregate, ternary ceramic precursor binder, composite functional additives, and precise preparation processes. Under low-carbon clean smelting conditions, it achieves a comprehensive improvement in high strength, high slag resistance, high oxidation resistance, high thermal shock stability, and high structural integrity, significantly extending the service life of refractory materials and better adapting to the harsh working conditions of high-end clean steel, special steel, and low-carbon metallurgy.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of ceramic refractory brick technology, specifically relating to an alumina ceramic-doped magnesia-carbon refractory brick and its preparation method. Background Technology
[0002] Magnesia-carbon refractory bricks, with their high refractoriness of magnesium oxide and excellent thermal shock resistance of graphite, have become a key lining material for high-temperature metallurgical equipment. However, with the advancement of clean steel, special steel smelting, and low-carbon metallurgy, the technological bottlenecks of traditional magnesia-carbon refractory bricks have become increasingly apparent. Firstly, insufficient oxidation resistance: at high temperatures, graphite is easily oxidized and decarburized, forming a loose, porous layer, resulting in a sharp drop in strength, increased slag penetration, and structural spalling. Secondly, an imbalance between low carbon content and performance: while reducing carbon content decreases carbon pollution from molten steel, the discontinuous carbon network leads to a significant decrease in thermal shock resistance and slag resistance, making it difficult to balance clean smelting with service life. Thirdly, poor high-temperature structural stability: magnesium oxide and carbon undergo reduction reactions under vacuum and high temperatures, causing brick deterioration; the oxidation and volume expansion of metallic antioxidants easily induces microcracks, reducing structural integrity. Fourthly, weak resistance to slag erosion: molten slag easily erodes the magnesium oxide matrix, accelerating the damage rate and shortening the lining life. These issues limit the adaptability of magnesia-carbon refractory bricks to high-end metallurgical applications. Therefore, it is necessary to achieve performance breakthroughs through component optimization and structural control. Summary of the Invention
[0003] To address the problems of insufficient oxidation resistance, low carbonization and performance imbalance, poor high-temperature structural stability, and weak resistance to slag erosion in existing traditional magnesia-carbon refractory bricks, this invention provides an alumina ceramic-doped magnesia-carbon refractory brick and its preparation method. Through the synergistic design of core-shell aggregates, multi-component ceramic precursor binders, and functional additives, it achieves a comprehensive improvement in high strength, high slag resistance, and oxidation resistance. The specific technical solution is as follows:
[0004] A type of alumina ceramic doped magnesia-carbon refractory brick is made from the following raw materials in parts by weight: 55-60 parts of core-shell modified fused magnesia aggregate, 18-20 parts of matrix functional powder, 12-15 parts of ternary ceramic precursor binder, 5-6 parts of composite functional additives, and 0.15-0.25 parts of dispersant.
[0005] The core-shell modified fused magnesia aggregate is fused magnesia with a double-layer coating. The inner layer is a SrO-CaO-Al2O3 glass phase, and the outer layer is an in-situ generated transition layer of MgAl2O4 and Al2O3. The matrix functional powder includes high-purity magnesia fine powder, tabular corundum, and flake graphite in a mass ratio of (40-45):(15-20):(8-12). The ternary ceramic precursor binder includes thermosetting liquid phenolic resin, liquid polycarbosilane, organopolyborosilicate precursor polymer, and platinum catalyst in a mass ratio of (45-50):(18-25):(13-17):(0.3-0.5). The composite functional additives include zirconium boride, boron carbide, and nano silicon carbide in a mass ratio of (5-7):(4-6):(2-3).
[0006] The particle size distribution of the core-shell modified fused magnesia aggregate in the above raw materials is as follows: 3mm < particle size ≤ 5mm accounts for 40wt% to 45wt%, 1mm < particle size ≤ 3mm accounts for 35wt% to 40wt%, and 0.1mm < particle size ≤ 1mm accounts for 15wt% to 20wt%.
[0007] The preparation method of the core-shell modified fused magnesia aggregate in the above raw materials includes: mixing and melting SrCO3:CaCO3:Al2O3 in a mass ratio of (1-2):(3-4):(5-7), water quenching and grinding to obtain glass powder; wet mixing, drying and sintering of fused magnesia:glass powder:anhydrous ethanol:polyvinyl butyral:boric acid = 100:(30-35):(0.6-0.8):(2-3):(1-2) in a mass ratio to obtain an intermediate; wet mixing of the intermediate with alumina sol containing titanium dioxide, drying and heat treatment at 1300-1400℃ to obtain the core-shell modified fused magnesia aggregate.
[0008] Furthermore, the preparation method of the core-shell modified fused magnesia aggregate includes: mixing SrCO3:CaCO3:Al2O3 in a mass ratio of (1-2):(3-4):(5-7), melting at 1550℃-1600℃, water quenching, and grinding to D50≤10μm to obtain glass powder; and mixing fused magnesia:glass powder:anhydrous ethanol:polyvinyl butyral:boric acid in a ratio of 100:(30-35):(0.6-0.8):(2-3). (1-2) By mass ratio, wet mix, dry, sinter at 1400℃-1500℃ for 2-2.5h to obtain an intermediate; add 0.3-0.5 times the mass of aluminum sol containing 0.5wt%-1wt% titanium dioxide and 12wt%-15wt% solid content to the intermediate, wet mix, pre-dry at 60℃-70℃, dry at 110℃-120℃, heat treat at 1300℃-1400℃ for 1-1.5h to obtain core-shell modified fused magnesia aggregate.
[0009] In the above raw materials, the D50 of the high-purity magnesia fine powder is ≤5μm.
[0010] In the above-mentioned raw materials, the D50 of the tabular corundum is 2μm to 8μm.
[0011] In the above raw materials, the flake graphite is sieved through a 100-150 mesh sieve.
[0012] In the above-mentioned raw materials, the platinum catalyst is an isopropanol solution with a platinum content of 0.5wt% to 1wt% prepared by using Karstedt catalyst and isopropanol.
[0013] In the above raw materials, the D50 of the zirconium boride is ≤5μm.
[0014] In the above raw materials, the boron carbide has a D50 ≤ 5 μm.
[0015] In the above raw materials, the D50 of the nano-silicon carbide is less than 100 nm.
[0016] The dispersant in the above raw materials is BYK-W969 dispersant.
[0017] The preparation method of the above-mentioned alumina ceramic-doped magnesia-carbon refractory brick includes the following steps: core-shell modified fused magnesia aggregate is dry-mixed evenly according to the mass fraction, matrix functional powder and composite functional additive are added and dry-mixed evenly to obtain dry material; ternary ceramic precursor binder and dispersant are added to the dry material and mixed evenly, and then the material is trapped to obtain plastic clay; the plastic clay is loaded into a mold, pre-pressed at 100MPa~120MPa, pressed into shape at 200MPa~220MPa, and demolded to obtain brick blank; the brick blank is dried and sintered to obtain refractory brick.
[0018] In the above-mentioned method for preparing refractory bricks, the drying parameters are: 40℃~50℃ for 12h~16h, 80℃~90℃ for 12h~16h, and 110℃~120℃ for 20h~24h.
[0019] In the above-mentioned method for preparing refractory bricks, the sintering parameters are as follows: sintering at 300℃ to 350℃ at a rate of 2℃ / min to 3℃ / min for 1h to 1.5h; sintering at 800℃ to 850℃ at a rate of 3℃ / min to 5℃ / min for 1.5h to 2h; sintering at 1300℃ to 1350℃ at a rate of 2℃ / min to 3℃ / min for 1h to 1.5h; and sintering at 1500℃ to 1550℃ at a rate of 2℃ / min to 3℃ / min for 2h to 3h.
[0020] The present invention provides an alumina ceramic-doped magnesia-carbon refractory brick and its preparation method, which have the following beneficial effects:
[0021] I. This invention addresses the problems of insufficient oxidation resistance, performance imbalance after low-carbonization, poor high-temperature structural stability, and weak slag erosion resistance in traditional magnesia-carbon refractory bricks through the synergistic design of core-shell modified fused magnesia aggregate, ternary ceramic precursor binder, composite functional additives, and precise preparation processes. Under low-carbon clean smelting conditions, it achieves a comprehensive improvement in high strength, high slag resistance, high oxidation resistance, high thermal shock stability, and high structural integrity, significantly extending the service life of refractory materials and better adapting to the harsh working conditions of high-end clean steel, special steel, and low-carbon metallurgy.
[0022] II. Core-shell modified fused magnesia aggregate: The inner SrO-CaO-Al2O3 glass phase softens and fills microcracks at high temperature, effectively blocking oxygen and slag from penetrating into the interior, inhibiting the high-temperature reduction reaction of magnesium oxide and carbon, and preventing brick deterioration; the outer layer generates an in-situ transition layer of magnesium aluminum spinel and alumina, with a thermal expansion coefficient highly matched with the matrix, eliminating interfacial thermal stress, significantly improving thermal shock stability, and enhancing the matrix's resistance to slag erosion, realizing the transformation of aggregate from passive tolerance to active protection.
[0023] III. Matrix Functional Powder: High-purity magnesia fine powder, tabular corundum and flake graphite are compounded in an optimized ratio to form a reasonable particle size distribution and a dense packing structure, which reduces carbon content while ensuring the strength of the matrix structure and thermal shock stability.
[0024] IV. Ternary ceramic precursor binder: Thermosetting phenolic resin provides room temperature bonding strength, ensuring molding and processing performance; liquid polycarbosilane and organoborosilicate precursor polymers generate silicon carbide, boron nitride and other ceramic phases in situ at high temperature, constructing a continuous high-temperature resistant ceramic network, solving the defect of discontinuous carbon network in low-carbon magnesia-carbon bricks; platinum catalyst promotes full cross-linking of precursors at low temperature, reduces porosity and defects, and significantly improves brick density and high-temperature strength.
[0025] V. Composite functional additives: Zirconium boride, boron carbide, and nano-silicon carbide are preferentially oxidized at high temperatures to generate a borosilicate glass phase that fills the pores and forms a dense anti-oxidation layer; nano-silicon carbide inhibits abnormal grain growth, stabilizes the high-temperature structure, and provides multi-level protection to synergistically enhance anti-oxidation, anti-slag, and anti-thermal shock properties.
[0026] VI. Dispersant: Improves the wettability and dispersion uniformity of powder, avoids particle agglomeration and local segregation, ensures uniform distribution of each functional phase, and further enhances the density and performance stability of brick.
[0027] VII. In the preparation method of refractory bricks: the brick blanks are dried using a stepped temperature control process involving low, medium, and high temperatures to slowly remove volatiles and solvents, avoiding internal stress and microcracks caused by rapid heating, and ensuring the integrity of the brick blank structure. The brick blanks are sintered in stages according to the laws of precursor decomposition, ceramic phase transformation, and structural densification, matching the material phase transformation and sintering process, ultimately obtaining dense, low-porosity, crack-free refractory bricks with excellent high-temperature performance. Detailed Implementation
[0028] The following provides some embodiments for further illustration, but the present invention is not limited to these embodiments.
[0029] Example 1
[0030] A type of alumina ceramic doped magnesia-carbon refractory brick is made from the following raw materials in parts by weight: 58 parts of core-shell modified fused magnesia aggregate, 19 parts of matrix functional powder, 13 parts of ternary ceramic precursor binder, 5.5 parts of composite functional additive, and 0.2 parts of dispersant.
[0031] In this embodiment, the core-shell modified fused magnesia aggregate is fused magnesia with a double-layer coating. The inner layer is a SrO-CaO-Al2O3 glass phase, and the outer layer is an in-situ generated transition layer of MgAl2O4 and Al2O3.
[0032] The particle size distribution of the core-shell modified fused magnesia aggregate and fused magnesia is as follows: 40 wt% for particles 3 mm < ≤ 5 mm, 40 wt% for particles 1 mm < ≤ 3 mm, and 20 wt% for particles 0.1 mm < ≤ 1 mm.
[0033] The preparation method of core-shell modified fused magnesia aggregate includes: mixing SrCO3:CaCO3:Al2O3 in a mass ratio of 1.5:3.5:6, melting at 1550℃~1600℃ for 2 hours, water quenching, and grinding to a D50 of 7.6μm to obtain glass powder. Wet mixing is then performed at a mass ratio of fused magnesia:glass powder:anhydrous ethanol:polyvinyl butyral:boric acid = 100:32:0.7:2.5:1.5, drying at 80℃~90℃ for 14 hours, and sintering at 1450℃ for 2 hours to coat the surface of the fused magnesia with a glass phase. The mixture is then cooled and dispersed to obtain an intermediate. The intermediate was added to an aluminum sol with a solid content of 13 wt% and containing 0.8 wt% titanium dioxide. The mixture was wet-mixed evenly, pre-dried at 60℃~70℃ for 7 h, dried at 110℃~120℃ for 14 h, heat-treated at 1350℃ for 1 h, dispersed, and graded to obtain core-shell modified fused magnesia aggregate.
[0034] In this embodiment, the matrix functional powder includes high-purity magnesia fine powder, tabular corundum, and flake graphite in a mass ratio of 43:18:10.
[0035] High-purity magnesia fine powder: D50 is 5μm, MgO content is 99wt%. Tabular corundum: α-Al2O3, D50 is 4.2μm, Al2O3 content is 99.2wt%. Flake graphite: passed through a 100-mesh sieve, C content is 99.8wt%.
[0036] In this embodiment, the ternary ceramic precursor binder includes a thermosetting liquid phenolic resin, liquid polycarbosilane, organopolyborosilicate precursor polymer, and platinum catalyst in a mass ratio of 48:22:15:0.4.
[0037] The platinum catalyst is a platinum-containing isopropanol solution prepared by reacting Karstedt catalyst with isopropanol, with a platinum content of 0.8 wt%.
[0038] In this embodiment, the composite functional additives include zirconium boride, boron carbide, and nano-silicon carbide in a mass ratio of 6:5:2.5.
[0039] Zirconium boride: D50 is 4.3 μm, purity is 98.4 wt%. Boron carbide: D50 is 4.8 μm, purity is 99.0 wt%. Nano silicon carbide: D50 is 50 nm, purity is 99.2 wt%.
[0040] In this embodiment, the dispersant is BYK-W969 dispersant.
[0041] The preparation method of the above-mentioned alumina ceramic-doped magnesia-carbon refractory brick includes the following steps:
[0042] S1, Dry Mixing: Add the core-shell modified fused magnesia aggregate to the mixer according to the mass fraction, and dry mix for 2 minutes; add the matrix functional powder and composite functional additives, and continue to dry mix for 7 minutes to obtain the dry material;
[0043] S2, wet mixing and aging: Add ternary ceramic precursor binder and dispersant to dry material, mix at 40℃ for 12 min; aging in an environment with humidity ≤40% and temperature range of 25℃~30℃ for 14 h to obtain plastic slurry;
[0044] S3, Molding: The plastic clay is loaded into the mold, pre-pressed at 110MPa for 2 minutes to expel the internal gas, pressed at 210MPa for 6 minutes, and demolded to obtain the brick blank.
[0045] S4, Drying: Place the brick blanks in a drying kiln and keep them at a temperature of 40℃~50℃ for 14 hours, 80℃~90℃ for 14 hours, and 110℃~120℃ for 22 hours to slowly remove the volatile solvents and prevent the brick blanks from cracking.
[0046] S5, sintering: sinter at 350℃ for 1 hour at 2℃ / min; sinter at 800℃ for 2 hours at 5℃ / min; sinter at 1350℃ for 1 hour at 2℃ / min; sinter at 1500℃ for 3 hours at 3℃ / min; cool with the furnace to obtain alumina-doped magnesia-carbon refractory bricks.
[0047] Example 2
[0048] A type of alumina ceramic doped magnesia-carbon refractory brick is made from the following raw materials in parts by weight: 55 parts of core-shell modified fused magnesia aggregate, 20 parts of matrix functional powder, 12 parts of ternary ceramic precursor binder, 6 parts of composite functional additive, and 0.15 parts of dispersant.
[0049] In this embodiment, the core-shell modified fused magnesia aggregate is fused magnesia with a double-layer coating. The inner layer is a SrO-CaO-Al2O3 glass phase, and the outer layer is an in-situ generated transition layer of MgAl2O4 and Al2O3.
[0050] The particle size distribution of the core-shell modified fused magnesia aggregate and fused magnesia is as follows: 3mm < particle size ≤ 5mm accounts for 45wt%, 1mm < particle size ≤ 3mm accounts for 35wt%, and 0.1mm < particle size ≤ 1mm accounts for 20wt%.
[0051] The preparation method of core-shell modified fused magnesia aggregate includes: mixing SrCO3:CaCO3:Al2O3 at a mass ratio of 1:4:5, melting at 1550℃~1600℃ for 2 hours, water quenching, and grinding to a D50 of 10.0μm to obtain glass powder. Wet mixing is then performed at a mass ratio of fused magnesia:glass powder:anhydrous ethanol:polyvinyl butyral:boric acid = 100:30:0.8:2:2, followed by drying at 80℃~90℃ for 12 hours, and sintering at 1500℃ for 2 hours to coat the surface of the fused magnesia with a glass phase. The mixture is then cooled and dispersed to obtain an intermediate. The intermediate was added to an aluminum sol with a solid content of 15 wt% and containing 0.5 wt% titanium dioxide. The mixture was wet-mixed evenly, pre-dried at 60℃~70℃ for 6 hours, dried at 110℃~120℃ for 16 hours, and heat-treated at 1300℃ for 1.5 hours. The mixture was then dispersed and graded to obtain core-shell modified fused magnesia aggregate.
[0052] In this embodiment, the matrix functional powder includes high-purity magnesia fine powder, tabular corundum, and flake graphite in a mass ratio of 40:15:8.
[0053] High-purity magnesia fine powder: D50 is 4.5μm, MgO content is 99.3wt%. Tabular corundum: α-Al2O3, D50 is 2.0μm, Al2O3 content is 99.4wt%. Flake graphite: passed through a 150-mesh sieve, C content is 99.5wt%.
[0054] In this embodiment, the ternary ceramic precursor binder includes a thermosetting liquid phenolic resin, liquid polycarbosilane, organopolyborosilicate precursor polymer, and platinum catalyst in a mass ratio of 45:18:13:0.3.
[0055] The platinum catalyst is a platinum-containing isopropanol solution prepared by reacting Karstedt catalyst with isopropanol, with a platinum content of 0.5 wt%.
[0056] In this embodiment, the composite functional additives include zirconium boride, boron carbide, and nano-silicon carbide in a mass ratio of 5:6:2.
[0057] Zirconium boride: D50 is 5.0 μm, purity is 98.0 wt%. Boron carbide: D50 is 3.8 μm, purity is 98.5 wt%. Nano silicon carbide: D50 is 80 nm, purity is 99.5 wt%.
[0058] In this embodiment, the dispersant is BYK-W969 dispersant.
[0059] The preparation method of the above-mentioned alumina ceramic-doped magnesia-carbon refractory brick includes the following steps:
[0060] S1, Dry Mixing: Add the core-shell modified fused magnesia aggregate to the mixer according to the mass fraction, and dry mix for 2 minutes; add the matrix functional powder and composite functional additives, and continue to dry mix for 6 minutes to obtain the dry material;
[0061] S2, wet mixing and aging: Add ternary ceramic precursor binder and dispersant to dry material, mix at 35℃ for 10 min; aging in an environment with humidity ≤40% and temperature range of 25℃~30℃ for 12 h to obtain plastic slurry;
[0062] S3, Molding: The plastic clay is loaded into the mold, pre-pressed at 100MPa for 2 minutes to expel the internal gas, pressed at 200MPa to form, held under pressure for 5 minutes, and demolded to obtain the brick blank.
[0063] S4, Drying: Place the brick blanks in a drying kiln and keep them at a temperature of 40℃~50℃ for 12 hours, 80℃~90℃ for 12 hours, and 110℃~120℃ for 20 hours to slowly remove the volatile solvents and prevent the brick blanks from cracking.
[0064] S5, sintering: sinter at 300℃ for 1 hour at 2℃ / min; sinter at 800℃ for 1.5 hours at 3℃ / min; sinter at 1300℃ for 1 hour at 2℃ / min; sinter at 1500℃ for 2 hours at 2℃ / min; cool with the furnace to obtain alumina-doped magnesia-carbon refractory bricks.
[0065] Example 3
[0066] A type of alumina ceramic doped magnesia-carbon refractory brick is made from the following raw materials in parts by weight: 60 parts of core-shell modified fused magnesia aggregate, 18 parts of matrix functional powder, 15 parts of ternary ceramic precursor binder, 5 parts of composite functional additive, and 0.25 parts of dispersant.
[0067] In this embodiment, the core-shell modified fused magnesia aggregate is fused magnesia with a double-layer coating. The inner layer is a SrO-CaO-Al2O3 glass phase, and the outer layer is an in-situ generated transition layer of MgAl2O4 and Al2O3.
[0068] The particle size distribution of the core-shell modified fused magnesia aggregate and fused magnesia is as follows: 3mm < particle size ≤ 5mm accounts for 45wt%, 1mm < particle size ≤ 3mm accounts for 40wt%, and 0.1mm < particle size ≤ 1mm accounts for 15wt%.
[0069] The preparation method of core-shell modified fused magnesia aggregate includes: mixing SrCO3:CaCO3:Al2O3 in a mass ratio of 2:3:7, melting at 1550℃~1600℃ for 2.5h, water quenching, and grinding to a D50 of 6.3μm to obtain glass powder. Wet mixing is then performed at a mass ratio of fused magnesia:glass powder:anhydrous ethanol:polyvinyl butyral:boric acid = 100:35:0.6:3:1, followed by drying at 80℃~90℃ for 16h, and sintering at 1400℃ for 2.5h to coat the surface of the fused magnesia with a glass phase. The mixture is then cooled and dispersed to obtain an intermediate. The intermediate was added to an aluminum sol with a solid content of 12 wt% containing 1 wt% titanium dioxide. The mixture was wet-mixed evenly, pre-dried at 60℃~70℃ for 8 hours, dried at 110℃~120℃ for 12 hours, and heat-treated at 1400℃ for 1 hour. The mixture was then dispersed and graded to obtain core-shell modified fused magnesia aggregate.
[0070] In this embodiment, the matrix functional powder includes high-purity magnesia fine powder, tabular corundum, and flake graphite in a mass ratio of 45:20:12.
[0071] High-purity magnesia fine powder: D50 is 3.8μm, MgO content is 99.1wt%. Tabular corundum: α-Al2O3, D50 is 8.0μm, Al2O3 content is 99wt%. Flake graphite: passed through a 150-mesh sieve, C content is 99.5wt%.
[0072] In this embodiment, the ternary ceramic precursor binder includes a thermosetting liquid phenolic resin, liquid polycarbosilane, organopolyborosilicate precursor polymer, and platinum catalyst in a mass ratio of 50:25:17:0.5.
[0073] The platinum catalyst is a platinum-containing isopropanol solution prepared by reacting Karstedt catalyst with isopropanol, with a platinum content of 1 wt%.
[0074] In this embodiment, the composite functional additives include zirconium boride, boron carbide, and nano-silicon carbide in a mass ratio of 7:4:3.
[0075] Zirconium boride: D50 is 3.9 μm, purity is 98.7 wt%. Boron carbide: D50 is 5.0 μm, purity is 98.0 wt%. Nano silicon carbide: D50 is 60 nm, purity is 99.0 wt%.
[0076] In this embodiment, the dispersant is BYK-W969 dispersant.
[0077] The preparation method of the above-mentioned alumina ceramic-doped magnesia-carbon refractory brick includes the following steps:
[0078] S1, Dry Mixing: Add the core-shell modified fused magnesia aggregate to the mixer according to the mass fraction, and dry mix for 3 minutes; add the matrix functional powder and composite functional additives, and continue to dry mix for 8 minutes to obtain the dry material;
[0079] S2, wet mixing and aging: Add ternary ceramic precursor binder and dispersant to dry material, mix at 45℃ for 15 min; aging in an environment with humidity ≤40% and temperature range of 25℃~30℃ for 16 h to obtain plastic slurry;
[0080] S3, Molding: The plastic clay is loaded into the mold, pre-pressed at 120MPa for 3 minutes to expel the internal gas, pressed at 220MPa for 8 minutes, and demolded to obtain the brick blank.
[0081] S4, Drying: Place the brick blanks in a drying kiln and keep them at a temperature of 40℃~50℃ for 16 hours, 80℃~90℃ for 16 hours, and 110℃~120℃ for 24 hours to slowly remove the volatile solvents and prevent the brick blanks from cracking.
[0082] S5, sintering: The brick blanks are sintered at 3℃ / min to 350℃ for 1.5h; sintered at 5℃ / min to 850℃ for 2h; sintered at 3℃ / min to 1350℃ for 1.5h; sintered at 3℃ / min to 1550℃ for 3h; cooled in the furnace to obtain alumina-doped magnesia-carbon refractory bricks.
[0083] In the above embodiments, the brick blanks are sintered in an oxygen-free manner.
[0084] The raw material specifications and sources involved in the above embodiments are as follows: The MgO purity of fused magnesia is above 98%. Polyvinyl butyral is sourced from Hubei Xinrunde Chemical Co., Ltd., with a purity of 99%. The aluminum sol is a nitric acid-based aluminum sol sourced from Zibo Ranxing Chemical Co., Ltd., diluted with nitric acid to a solid content of 12wt%–15wt%. The TiO2 is rutile titanium dioxide with a purity above 98% and a median particle size below 1μm. The thermosetting liquid phenolic resin is sourced from Jining Huakai Resin Co., Ltd., with a viscosity of 4700–5800 mPa·s, a solid content of 75.5–78.5% at 150℃, a residual carbon content of 45–48%, a free phenol content of 8.0–10.0%, and a pH of 6.5–7.0. The liquid polycarbosilane was sourced from Zibo Linzi Qiquan Industry and Trade Co., Ltd., with a viscosity (25℃) / mPa·s of ≤100, a ceramic yield of the cured product (1100℃, argon) / wt% of ≥80.0, and an oxygen content of the pyrolysis products / (1100℃) / wt% of ≤2.5. The organoborosilicate precursor polymer was sourced from Anhui Aiyota Silicon Oil Co., Ltd., IOTA-9120. The Karstedt catalyst was sourced from Hubei Nuona Technology Co., Ltd. The BYK-W969 dispersant was a BYK-W969 wetting and dispersing agent. All other unlisted raw materials had a purity of ≥98%.
[0085] Comparative Example 1
[0086] The difference from Example 1 is that the core-shell modified fused magnesia aggregate is directly replaced by fused magnesia.
[0087] Comparative Example 2
[0088] The difference from Example 1 is that the core-shell modified fused magnesia aggregate is directly replaced by an intermediate (the intermediate is directly broken down and graded to obtain aggregate without secondary coating).
[0089] Comparative Example 3
[0090] The difference from Example 1 is that no intermediate is prepared. Instead, fused magnesia is directly added to 0.4 times its mass of aluminum sol, which is a 13wt% aluminum sol containing 0.8wt% titanium dioxide. The mixture is wet-mixed evenly, pre-dried at 60℃~70℃ for 7h, dried at 110℃~120℃ for 14h, heat-treated at 1350℃ for 1h, dispersed, and graded to obtain core-shell modified fused magnesia aggregate.
[0091] Comparative Example 4
[0092] The difference from Example 1 is that no polyvinyl butyral and boric acid are added in the preparation of the core-shell modified fused magnesia aggregate.
[0093] Comparative Example 5
[0094] The difference from Example 1 is that the ternary ceramic precursor binder is entirely replaced by thermosetting liquid phenolic resin.
[0095] Comparative Example 6
[0096] The difference from Example 1 is that the ternary ceramic precursor binder does not contain organic polyborosilazane precursor polymer and platinum catalyst.
[0097] Comparative Example 7
[0098] The difference from Example 1 is that BYK-W969 dispersant is not added.
[0099] Comparative Example 8
[0100] The difference from Example 1 is that the brick drying process is changed to: direct heat treatment at 110℃~120℃ for 22h; the brick sintering process is changed to: sintering at 350℃ for 1h at 5℃ / min; sintering at 800℃ for 2h at 5℃ / min; and sintering at 1350℃ for 1h at 5℃ / min.
[0101] Comparative Example 9
[0102] The difference from Example 1 is that 6 parts of ternary ceramic precursor binder were added.
[0103] Comparative Example 10
[0104] The difference from Example 1 is that 30 parts of ternary ceramic precursor binder are added.
[0105] I. Bulk density and apparent porosity:
[0106] Sample specifications: 50mm×50mm×50mm cube, allowable deviation ±0.5mm, 3 parallel samples.
[0107] Test Procedure: According to GB / T 2997 "Test Methods for Bulk Density, Apparent Porosity and True Porosity of Dense Shaped Refractory Products", the sample is dried in an oven at 110℃±5℃ to constant weight. The difference between two consecutive weighings is ≤0.1%, and the dried mass m0 is measured. The sample is then placed in a vacuum device, and a vacuum of 0.095MPa is applied for 2 hours. It is then immersed in water (20℃±5℃) for 1 hour. The mass m1 of the saturated sample in air and the mass m2 of the saturated sample in water are measured. Density ρ0 = m0 × ρwater / (m1−m2), where ρwater is taken as 1.00 g / cm³. 3 Apparent porosity Pa = (m1−m0) / (m1−m2)×100%.
[0108] II. Compressive strength at room temperature:
[0109] Sample specifications: a cylinder with a diameter of 50mm ± 0.5mm and a height of 50mm ± 0.5mm, with 3 parallel samples.
[0110] Test Procedure: According to GB / T 5072 "Test Method for Compressive Strength of Refractory Materials at Room Temperature", the specimens were dried to constant weight in an oven at 110℃±5℃; a constant loading rate of 0.5MPa / s was applied until the specimen failed, and the maximum failure load F was recorded. σ=F / S, where: σ is the compressive strength at room temperature (MPa), F is the maximum load at specimen failure (N), and S is the original cross-sectional area of the pressure-bearing surface of the specimen (mm²). 2 ).
[0111] III. Flexural strength at room temperature:
[0112] Sample specifications: 150mm×25mm×25mm cuboid, 3 parallel samples.
[0113] Test procedure: According to GB / T 3001 "Test Method for Flexural Strength of Refractory Materials at Room Temperature", the span is 100 mm; the sample is loaded at a loading rate of 0.15 MPa / s until it fractures, and the maximum breaking load F is recorded. R = 3FL / (2bh) 2 In the formula: R is the flexural strength at room temperature (MPa), F is the maximum load when the specimen breaks (N), L is the distance between the lower cutting edges (mm), b is the width of the specimen (mm), and h is the height of the specimen (mm).
[0114] IV. Flexural strength at 1400℃:
[0115] Sample specifications: 150mm×25mm×25mm cuboid, 3 parallel samples.
[0116] Test Procedure: According to GB / T 3002 "Test Method for High-Temperature Flexural Strength of Refractory Materials", the test was conducted under a nitrogen protective atmosphere, with the temperature raised to 1400℃ and held for 30 min; a loading rate of 0.15 MPa / s was applied until the specimen fractured, and the maximum breaking load F was recorded. R = 3FL / (2bh) 2 In the formula: R is the high temperature flexural strength (MPa), F is the maximum load when the specimen breaks (N), L is the distance between the lower cutting edges (mm), b is the specimen width (mm), and h is the specimen height (mm).
[0117] V. Permanent linear changes after heating at 1500℃:
[0118] Sample specifications: 50mm×50mm×60mm cuboid, 3 parallel samples.
[0119] Test procedure: According to GB / T 5988 "Test method for permanent linear change of refractory materials under heating", measure the original length L0 of the sample; place the sample in a sintering furnace, under nitrogen protection, heat to 1500℃ and hold for 3 hours, then cool with the furnace; remove the sample and measure the length L1 after cooling. The rate of permanent linear change under heating ΔL = (L1−L0) / L0×100%.
[0120] VI. Antioxidant performance at 1400℃:
[0121] Sample specifications: 50mm×50mm×50mm cube, 3 parallel samples.
[0122] Test Procedure: According to GB / T 13244 "Test Method for Oxidation Resistance of Carbon-Containing Refractory Materials", measure the original mass m0 of the sample; place the sample in a high-temperature furnace and heat it to 1400℃ at a rate of 5℃ / min under air atmosphere, holding it at that temperature for 2 hours; cool it to room temperature with the furnace, remove the sample, and measure the mass m1 after oxidation. Oxidation weight loss rate Δm = (m0−m1) / m0×100%.
[0123] VII. Thermal shock stability at 1100℃:
[0124] Sample specifications: 230mm×114mm×65mm straight brick, 3 parallel samples.
[0125] Test procedure: According to GB / T 30873 "Test method for thermal shock resistance of refractory materials" (Method 1: water quenching method - straight brick specimen), place the specimen in a high-temperature furnace, heat to 1100℃ and hold for 30 min; remove the specimen and quickly immerse it in flowing water at 20℃ for 3 min; remove the specimen and dry it at 110℃ to constant weight; repeat the above thermal shock cycle until the specimen shows through cracks; record the number of complete cycles that the specimen can withstand.
[0126] 8. Resistance to slag erosion at 1600℃:
[0127] Sample specifications: 70mm×70mm×70mm cube. A crucible hole with an inner diameter of 40mm and a depth of 35mm is drilled in the center of the top surface of the sample. Three parallel samples are prepared.
[0128] Test procedure: According to GB / T 8931 "Test method for slag resistance of refractory materials" (static crucible method), slag (mass ratio of molten slag CaO:SiO2:Fe2O3:Al2O3=45:35:15:5, slag amount is 2 / 3 of the crucible hole volume) is added into the crucible hole. The sample is placed in the sintering furnace and heated to 1600℃ at 5℃ / min and held for 3h. It is then cooled to room temperature with the furnace. The sample is cut vertically along the central axis and the maximum depth of slag erosion on the cross-section is measured.
[0129] Table 1. Test Results (Average Values)
[0130]
[0131] The superior performance of Examples 1 to 3 stems from the synergistic effect of core-shell modified fused magnesia aggregate, ternary ceramic precursor binder, composite functional additives, and precise processing. In the core-shell modified fused magnesia aggregate, the inner SrO-CaO-Al2O3 glassy phase softens and fills cracks at high temperatures, blocks oxygen and slag, and inhibits the reduction reaction of MgO and C. The outer layer generates an in-situ transition layer of MgAl2O4 and Al2O3, which eliminates interfacial stress through thermal expansion matching, improves thermal shock stability, and enhances resistance to acid and low-alkalinity slag erosion, achieving active protection of the aggregate. In the ternary ceramic precursor binder, phenolic resin provides room-temperature bonding strength; polycarbosilane and polyboronsilazane generate silicon carbide, BN, and other ceramic phases in-situ at high temperatures, constructing a continuous high-temperature ceramic network and solving the problem of discontinuous carbon networks under low-carbon conditions; the platinum catalyst promotes low-temperature cross-linking of the precursor, reduces porosity defects, and improves density and high-temperature strength. In the synergistic protection of composite functional additives, zirconium boride, boron carbide, and nano-silicon carbide are preferentially oxidized at high temperatures, generating B2O3 and SiO2 glass phases to fill the pores and form a dense antioxidant layer. Nano-silicon carbide inhibits grain growth and enhances high-temperature structural stability, with multi-level protection improving oxidation and corrosion resistance. Multi-grade aggregate gradation achieves close packing; gradient drying and segmented sintering avoid microcracks, and oxygen-free sintering reduces carbon oxidation, ultimately obtaining a high-density, low-porosity, high-strength, and high-durability microstructure.
[0132] Comparative Example 1 uses fused magnesia to replace core-shell modified fused magnesia aggregate. The inner SrO-CaO-Al2O3 glassy phase forms a dense, adhesive layer at high temperatures, preventing oxygen and slag from penetrating into the aggregate and inhibiting the high-temperature reduction reaction of MgO and C. The outer layer forms an in-situ transition layer of MgAl2O4 and Al2O3, with a thermal expansion coefficient matching the magnesia matrix, eliminating interfacial thermal stress, improving thermal shock stability, and the Al2O3 doping enhances the matrix's resistance to slag erosion. Unmodified fused magnesia lacks the performance advantages of the coating layer, has weak aggregate-matrix interfacial bonding, is prone to cracking due to thermal stress, and exhibits deterioration in various properties.
[0133] In Comparative Example 2, the core-shell modified fused magnesia aggregate only has an inner glass layer and no outer ceramic layer. The inner glass layer only provides basic adhesion and oxygen barrier, without an outer MgAl2O4 and Al2O3 transition layer, resulting in poor thermal expansion matching and easy formation of microcracks at the interface; insufficient slag resistance, allowing molten slag to easily penetrate along the cracks, and reduced high-temperature strength and thermal shock resistance.
[0134] In Comparative Example 3, the core-shell modified fused magnesia aggregate was only coated with alumina sol without an inner glass layer. There was no glass phase transition, the coating layer was not tightly bonded and easily detached, failing to form a continuous barrier layer; oxygen and slag could still penetrate the interior, the MgO-C reduction reaction was not inhibited, microcracks increased, and density and durability decreased.
[0135] In Comparative Example 4, the core-shell modified fused magnesia aggregate was prepared without PVB and boric acid. The absence of PVB led to uneven glass powder coating, and the absence of boric acid affected the low-temperature sintering of the glass. The inner glass phase contained defects such as pores and cracks. These defects became erosion channels, the interface was not tightly bonded, and it was easy to peel off during thermal shock, resulting in low overall performance.
[0136] Comparative Example 5 uses a phenolic resin binder. With only a carbon-bound phase, it is prone to oxidation and failure at high temperatures, lacking a ceramic phase to support the high-temperature structure; high-temperature strength, oxidation resistance, and thermal shock resistance are reduced, and molten slag and oxygen easily penetrate, increasing the depth of erosion.
[0137] In Comparative Example 6, the ternary ceramic precursor binder lacked polyborosilazane and platinum catalyst. The absence of a boron source and efficient catalysis resulted in a ceramic phase dominated by silicon carbide with insufficient network integrity; incomplete precursor cross-linking led to volatile matter escape and pore formation, resulting in decreased density and weakened high-temperature reinforcement, oxidation resistance, and slag resistance.
[0138] In Comparative Example 7, no dispersant was added. The powder and additives were not mixed evenly, resulting in local agglomeration and the formation of pores and loose zones inside, which increased the apparent porosity and decreased the density. The functional phase could not act uniformly, and the mechanical properties, oxidation resistance, and slag resistance were slightly deteriorated.
[0139] Comparative Example 8: Rapid drying and sintering of brick blanks. Rapid drying caused the solvent to evaporate rapidly, resulting in microcracks; rapid heating caused the precursor to decompose too quickly, stress concentration, and crack propagation; insufficient ceramic phase transformation resulted in poor structural integrity and a comprehensive decline in thermal shock resistance, oxidation resistance, and slag resistance.
[0140] In Comparative Example 9, the amount of binder in the ternary ceramic precursor was insufficient. The binder phase was insufficient to fully encapsulate the particles, resulting in low molding density. The amount of high-temperature ceramic phase generated was insufficient, the network was discontinuous, and the strength and high-temperature stability were slightly reduced. However, the synergistic effect of the core-shell and additives was retained, and the performance was still better than most of the defective groups.
[0141] In Comparative Example 10, the binder in the ternary ceramic precursor was excessive. Excessive precursor decomposes at high temperature, generating a large amount of gas, forming closed pores and internal stress, resulting in decreased density and increased brittleness; it also disrupts the gradation balance, making particle rearrangement difficult, and deteriorating mechanical, thermal shock, and slag resistance properties.
Claims
1. An alumina ceramic-doped magnesia-carbon refractory brick, characterized in that, Refractory bricks are made from the following raw materials in parts by weight: 55 to 60 parts of core-shell modified fused magnesia aggregate, 18 to 20 parts of matrix functional powder, 12 to 15 parts of ternary ceramic precursor binder, 5 to 6 parts of composite functional additives, and 0.15 to 0.25 parts of dispersant. The core-shell modified fused magnesia aggregate is fused magnesia with a double-layer coating. The inner layer is a SrO-CaO-Al2O3 glass phase, and the outer layer is an in-situ generated transition layer of MgAl2O4 and Al2O3. The matrix functional powder includes high-purity magnesia fine powder, tabular corundum, and flake graphite in a mass ratio of (40-45):(15-20):(8-12). The ternary ceramic precursor binder includes thermosetting liquid phenolic resin, liquid polycarbosilane, organopolyborosilicate precursor polymer, and platinum catalyst in a mass ratio of (45-50):(18-25):(13-17):(0.3-0.5). The composite functional additives include zirconium boride, boron carbide, and nano silicon carbide in a mass ratio of (5-7):(4-6):(2-3).
2. The alumina ceramic-doped magnesia-carbon refractory brick according to claim 1, characterized in that, The particle size distribution of the core-shell modified fused magnesia aggregate is as follows: 3mm < particle size ≤ 5mm accounts for 40wt% to 45wt%, 1mm < particle size ≤ 3mm accounts for 35wt% to 40wt%, and 0.1mm < particle size ≤ 1mm accounts for 15wt% to 20wt%.
3. The alumina ceramic-doped magnesia-carbon refractory brick according to claim 1, characterized in that, The preparation method of the core-shell modified fused magnesia aggregate includes: mixing and melting SrCO3:CaCO3:Al2O3 in a mass ratio of (1-2):(3-4):(5-7), water quenching and grinding to obtain glass powder; wet mixing, drying and sintering of fused magnesia:glass powder:anhydrous ethanol:polyvinyl butyral:boric acid in a mass ratio of 100:(30-35):(0.6-0.8):(2-3):(1-2) to obtain an intermediate; wet mixing of the intermediate with alumina sol containing titanium dioxide, drying and heat treatment at 1300-1400℃ to obtain the core-shell modified fused magnesia aggregate.
4. An alumina ceramic-doped magnesia-carbon refractory brick according to claim 1 or 3, characterized in that, The preparation method of the core-shell modified fused magnesia aggregate includes: mixing SrCO3:CaCO3:Al2O3 in a mass ratio of (1-2):(3-4):(5-7), melting at 1550℃-1600℃, water quenching, and grinding to D50≤10μm to obtain glass powder; and mixing fused magnesia:glass powder:anhydrous ethanol:polyvinyl butyral:boric acid = 100:(30-35):(0.6-0.8):(2-3):(1 ~2) By mass ratio, wet mix, dry, sinter at 1400℃~1500℃ for 2h~2.5h to obtain an intermediate; add 0.3~0.5 times the mass of aluminum sol containing 0.5wt%~1wt% titanium dioxide and a solid content of 12wt%~15wt% to the intermediate, wet mix, pre-dry at 60℃~70℃, dry at 110℃~120℃, heat treat at 1300℃~1400℃ for 1h~1.5h to obtain core-shell modified fused magnesia aggregate.
5. The alumina ceramic-doped magnesia-carbon refractory brick according to claim 1, characterized in that, The high-purity magnesia fine powder has a D50 ≤ 5μm; the tabular corundum has a D50 of 2μm to 8μm; and the flake graphite passes through a 100-150 mesh sieve.
6. The alumina ceramic-doped magnesia-carbon refractory brick according to claim 1, characterized in that, The platinum catalyst is a platinum content of 0.5wt% to 1wt% isopropanol solution prepared by using Karstedt catalyst and isopropanol.
7. The alumina ceramic-doped magnesia-carbon refractory brick according to claim 1, characterized in that, The zirconium boride has a D50 ≤ 5 μm; the boron carbide has a D50 ≤ 5 μm; and the nano-silicon carbide has a D50 < 100 nm.
8. The alumina ceramic-doped magnesia-carbon refractory brick according to claim 1, characterized in that, The dispersant is BYK-W969 dispersant.
9. The method for preparing an alumina ceramic-doped magnesia-carbon refractory brick according to claim 1, characterized in that, The process includes the following steps: Mixing core-shell modified fused magnesia aggregate evenly by mass fractions, adding matrix functional powder and composite functional additives, and mixing evenly to obtain dry material; adding ternary ceramic precursor binder and dispersant to the dry material and mixing evenly, then binding the material to obtain plastic clay; loading the plastic clay into a mold, pre-pressing at 100MPa~120MPa, pressing at 200MPa~220MPa to form the refractory brick; drying and sintering the brick to obtain refractory bricks.
10. The method for preparing an alumina ceramic-doped magnesia-carbon refractory brick according to claim 9, characterized in that, The drying parameters are: holding at 40℃~50℃ for 12h~16h, holding at 80℃~90℃ for 12h~16h, and holding at 110℃~120℃ for 20h~24h; the sintering parameters are: sintering at 2℃ / min~3℃ / min to 300℃~350℃ for 1h~1.5h; sintering at 3℃ / min~5℃ / min to 800℃~850℃ for 1.5h~2h; sintering at 2℃ / min~3℃ / min to 1300℃~1350℃ for 1h~1.5h; and sintering at 2℃ / min~3℃ / min to 1500℃~1550℃ for 2h~3h.
Citation Information
Patent Citations
Magnesia carbon brick with high slag resistance and low emission and preparation method thereof
CN121779132A
Non-slumping sprayable refractory castables containing thermal black
US6313056B1